Oxidative stress response in an anaerobe, Bacteroides fragilis: a role for catalase in protection against hydrogen peroxide. - Rocha, Edson R.; Selby, Tina; Coleman, James P.; Smith, C. Jeffrey (East Carolina University, 1996)
Survival of Bacteroides fragilis in the presence of oxygen was dependent on the ability of bacteria to synthesize new proteins, as determined by the inhibition of protein synthesis after oxygen exposure. The B. fragilis protein profile was significantly altered after either a shift from anaerobic to aerobic conditions with or without paraquat or the addition of exogenous hydrogen peroxide. As determined by autoradiography after twodimensional gel electrophoresis, approximately 28 newly synthesized proteins were detected in response to oxidative conditions. These proteins were found to have a broad range of pI values (from 5.1 to 7.2) and molecular weights (from 12,000 to 79,000). The hydrogen peroxide- and paraquat-inducible responses were similar but not identical to that induced by oxygen as seen by two-dimensional gel protein profile. Eleven of the oxidative response proteins were closely related, with pI values and molecular weights from 5.1 to 5.8 and from 17,000 to 23,000, respectively. As a first step to understanding the resistance to oxygen, a catalase-deficient mutant was constructed by allelic gene exchange. The katB mutant was found to be more sensitive to the lethal effects of hydrogen peroxide than was the parent strain when the ferrous iron chelator bipyridyl was added to culture media. This suggests that the presence of ferrous iron in anaerobic culture media exacerbates the toxicity of hydrogen peroxide and that the presence of a functional catalase is important for survival in the presence of hydrogen peroxide. Further, the treatment of cultures with a sublethal concentration of hydrogen peroxide was necessary to induce resistance to higher concentrations of hydrogen peroxide in the parent strain, suggesting that this was an inducible response. This was confirmed when the bacterial culture, treated with chloramphenicol before the cells were exposed to a sublethal concentration of peroxide, completely lost viability. In contrast, cell viability was greatly preserved when protein synthesis inhibition occurred after peroxide induction. Complementation of catalase activity in the mutant restored the ability of the mutant strain to survive in the presence of hydrogen peroxide, showing that the catalase (KatB) may play a role in oxidative stress resistance in aerotolerant anaerobic bacteria. Originally published Journal of Bacteriology, Vol. 178, No. 23, Dec. 1996
Keywords: Oxidative stress; Catalase; Hydrogen peroxide resistance